Implementasi Sistem PJU Otomatis Berbasis Sensor LDR Di Kampung Cikandang Setu, Desa Mekarsari - Erik Agustian Yulanda; Bambang Iwan Suryana; M. Syekhurohim; Agus Noviandi; Akmal Mubarok; Eksan Maulana Sidik; Lukman Maulana; Muhammad Rizki (CV. Multi Kreasi Media, 2026)
Public street lighting plays an important role in supporting safety and comfort for community activities during nighttime. Kampung Cikandang Setu, Desa Mekarsari, continues to experience limitations in street lighting facilities and inefficient lamp operation systems. This Community Service activity aims to implement an automatic Public Street Lighting (PJU) system based on a Light Dependent Resistor (LDR) sensor as an energy-efficient and user-friendly lighting solution. The implementation method includes field observation, system design, and installation of five PJU units using LED lamps integrated with LDR sensors, accompanied by community maintenance education. The results demonstrate that the automatic PJU system operates stably by controlling lamp operation according to ambient light intensity. System implementation improves road lighting quality, supports electrical energy efficiency, and enhances community safety. Community involvement during installation and educational activities strengthens technological understanding and supports sustainable utilization of the PJU system. The implementation of an LDR-based automatic PJU system shows strong potential as an effective and sustainable street lighting solution for rural areas.